Comparative study of the effects of the three kinds of Kampo-hozai: Ninjinyoeito, Hochuekkito, and Juzentaihoto on anxious and low sociability behavior using NPY-knockout zebrafish - Kawabe, Momoko; Nishida, Takumi; Takahashi, Ryuji; Inui, Akio; Shiozaki, Kazuhiro (Frontiers in Pharmacology, 2023)
Ninjinyoeito (NYT), Hochuekkito (HET), and Juzentaihoto (JTT) are the three types of Kampo-hozai used to support the treatment of various diseases by energizing patients through improved mental health. While Kampo-hozais are clinically used to improve mental energy decline, a comparison between their effects on neuropsychiatric symptoms like anxiety and sociability and the strength of their effects has not been conducted. Therefore, this study compared the effects of NYT, HET, and JTT on psychiatric symptoms using neuropeptide Y knockout (NPY-KO) zebrafish, a suitable animal model for anxiety and low sociability. NPY-KO zebrafish were fed a NYT, HET, or JTT-supplemented diet for four days. Then, sociability was analyzed using a three-Chambers test and anxiety-like behavior was evaluated using the cold stress and novel tank tests. The results showed that NYT treatment improved the low sociability of NPY-KO, while HET and JTT did not. NPY-KO exhibited anxiety-like behaviors, such as freezing and swimming in the wall area under cold stress, but NYT treatment improved these behaviors. However, these anxiety-like behaviors were not improved by HET and JTT. NYT treatment also improved anxiety-like behaviors of NPY-KO in the novel tank test. However, no improvement was shown in the HET and JTT groups. This trend was also confirmed in the low water stress test using wild-type zebrafish. This study exhibits that among the three types of Kampo-hozai, NYT is the most effective in psychiatric disorders associated with anxiety and low sociability.